Case report of urinary tract infection in sows of a commercial pig unit - SAOULIDIS (Κ. ΣΑΟΥΛΙΔΗΣ) K.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ) S. K.; SARRIS (Κ. ΣΑΡΡΗΣ) K.; ROUBIES (Ν. ΡΟΥΜΠΙΕΣ) N.; KYRIAKIS (Σ.K. ΚΥΡΙΑΚΗΣ) S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this paper, a case of urinary tract infection in sows of a commercial pig unit is presented for the first time in Greece. Within a period of one year, 21 cases of specific infection were recorded, representing 5.8% of the farrowings in the farm. The symptoms were obvious around the 3rd to 4th week post mating and were keeping on for 2 to 7 days. Anorexia, thirst, blood in the urine and subsequent death or survival with gradual loss of body condition were the main findings. A significant correlation between the number of sows that died, and the number of sows showing anorexia (p<0,05), or showing hypothermia (p<0,05) was observed. The average number of live born piglets at the last parturition compared to the respective figure during the previous parturitions was markedly reduced (p<0,05). The findings of microscopic and biochemical examination of the urine were indicative of infection, while biochemical examinations of blood samples of diseased sows have shown significantly increased urea (BUN) and creatinine levels (p<0,05). Bacteriological culture of urine samples have shown the presence of increased numbers of bacteria (>106/ml) such as Escherichia coli and Actinomyces suis in almost all ill sows. It is concluded that porcine urinary tract infections may cause serious problems for pig enterprises as may be directly correlated with reproductive performance and viability of the sows.